KLASIFIKASI EMOSI TOKOH DALAM NOVEL RASA KARYA TERE LIYE - Samsuryani, Dewi Lilik; Wartiningsih, Agus; Sanulita, Henny (Universitas Tanjungpura, 2025)
Emotions are activities or states of an individual's thoughts, feelings, and passions that are too excessive. This research aims to (1) analyze the classification of characters' emotions, (2) analyze the techniques of painting emotions experienced by characters in the novel Rasa by Tere Liye with a psychological approach by David Krech, and (3) create a teaching module using the novel Rasa by Tere Liye. The form of research used is qualitative with descriptive methods and David Krech's literary psychology research approach. The source of data in this study is the novel Rasa by Tere Liye and the data in this study is in the form of quotes or sentences that contain emotional classifications. The data analysis techniques carried out are data reduction, data presentation, and conclusion drawn. The results of this study show that the most emotional classification experienced by the characters in the novel Rasa by Tere Liye is the emotion of sadness. The most dominant painting technique used in Tere Liye's novel Rasa is a dramatic technique that is further divided into conversation, behavior, thoughts and feelings, consciousness flows, and character reactions. The resulting teaching module is in the form of an Indonesian subject teaching module that is used in the learning process at the high school level in grade XII phase F with learning materials in the form of novels and learning models in the form of Problem Based Learning (PBL).